In and out of the studio - McCartney, Andra (Université Concordia, 2013)
In and out of the studio was a collaborative multimedia project which aimed to examine and document the working methods of several female sound producers, from a variety of media (such as radio, film sound, television, hypermedia, performance art) and in different institutional contexts. The website, which is compiled in this document, was one element in an effort to establish a greater sense of community among women sound producers who are separated by geographic space, occupation or disciplinary boundaries.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Accepted: 2012-11-14T10:25:30Z Publisher: University of Exeter